Isolation of a cDNA Encoding a Granule-Bound 152-Kilodalton Starch-Branching Enzyme in Wheat - Båga, Monica (American Society of Plant Physiologists, 2000)
Screening of a wheat (Triticum aestivum) cDNA library for starch-branching enzyme I (SBEI) genes combined with 5′-rapid amplification of cDNA ends resulted in isolation of a 4,563-bp composite cDNA, Sbe1c. Based on sequence alignment to characterized SBEI cDNA clones isolated from plants, the SBEIc predicted from the cDNA sequence was produced with a transit peptide directing the polypeptide into plastids. Furthermore, the predicted mature form of SBEIc was much larger (152 kD) than previously characterized plant SBEI (80–100 kD) and contained a partial duplication of SBEI sequences. The first SBEI domain showed high amino acid similarity to a 74-kD wheat SBEI-like protein that is inactive as a branching enzyme when expressed in Escherichia coli. The second SBEI domain on SBEIc was identical in sequence to a functional 87-kD SBEI produced in the wheat endosperm. Immunoblot analysis of proteins produced in developing wheat kernels demonstrated that the 152-kD SBEIc was, in contrast to the 87- to 88-kD SBEI, preferentially associated with the starch granules. Proteins similar in size and recognized by wheat SBEI antibodies were also present in Triticum monococcum, Triticum tauschii, and Triticum turgidum subsp. durum.